Analysis of Benefits and Barriers Factors in the Implementation of Building Information Modeling (BIM) in Building Construction for Contractor - Gustian, Egi; Milyardi, Roi; Lesmana, Cindrawaty (Universitas Negeri Semarang, 2022)
Abstract. Everywhere in the world, especially as the fourth industrial revolution begins, technological advancements are being discussed. This technological advancement also affects the building industry, one example being the use of Building Information Modeling (BIM) technology. All technologies, particularly BIM, will advance and redevelop throughout this Covid-19 epidemic. BIM has benefits and barriers to implementation that increase with its development and sophistication, particularly for contractors. Therefore, it's important to research the advantages of using BIM as well as the barriers for contractors. The purpose of this study is to analyze the benefits and inhibiting factors in the implementation of BIM in building construction for contractor. This research was conducted by using literature from previous studies to find out what statements are the benefits and barrier factors in the implementation of BIM 4D for contractors with top and middle qualifications. Then the statement was compiled into a questionnaire and distributed to respondents via online platform. In addition to obtaining the mean value for each research variable, the questionnaire survey responses were processed utilizing validity and reliability tests. The findings of this study show that the benefits of BIM implementation for top contractors include better and more appealing building design or modeling, more accurate documentation, as well as better and more attractive building design or modeling for middle contractors. The lack of training and education in BIM itself is the main obstacle to its implementation for these top contractors, while the cost of licensing BIM software or apps is fairly high for midrange contractors.